Neurosyphilis Surveillance: Exploring the Use of Multiple Data Sources to Better Understand Morbidity in California. (August 2021) - Burghardt, Nicole Olson; Nelson, Lauren N.; Tang, Eric C.; Plotzker, Rosalyn E.; Jacobson, Kathleen; Murphy, Ryan D.
Abstract : Abstract: Accurate reporting of neurosyphilis diagnoses is important to quantify and monitor severe outcomes associated with infection of Treponemal pallidum . This analysis compared the demographic distribution of neurosyphilis diagnoses in sexually transmitted disease surveillance data with administrative hospital data in the California Project Area from 2016 to 2018. Although neurosyphilis morbidity was similar, significant differences were noted by sex, age group, race/ethnicity, and region. Both sexually transmitted disease surveillance and administrative hospital data may be imperfect systems to understand the true morbidity of neurosyphilis. Abstract : Both routine sexually transmitted disease surveillance and administrative hospital data may be imperfect systems to understand the true morbidity of neurosyphilis within the California Project Area from 2016 to 2018.Supplemental digital content is available in the text.